Investigation of the Use of Wood Based Materials in Friction Welding Method Applications - Zor, Mustafa (Bartın Üniversitesi, 2019)
The friction welding procedure, which is the method of mechanically connecting two parts together to obtain new, environmentally friendly products without using glue, metal or any fasteners, has revealed a new method. This method, which has recently been applied to the solid wood, is used to investigate the variation of wood properties on the welding parameters. If this method actually produces good results, the future of forest products industry will change significantly. This new method of combining solid wood with mechanical means can be used in many engineering applications due to advanced technology.

Tutkal, metal veya herhangi bir bağlayıcı kullanmadan yeni, çevre dostu ürünler elde etmek için iki parçayı mekanik olarak birbirine bağlama tekniği olan sürtünme kaynak uygulaması yeni bir yöntem olarak ortaya çıkmaktadır. Son zamanlarda masif ahşaba uygulanan bu yöntem, kaynak parametreleri üzerine ahşabın özelliklerinin değişimini araştırmak için kullanılmaktadır. Bu yöntem gerçekten iyi sonuçlar verirse, orman ürünleri endüstrisinin geleceğini önemli ölçüde değiştirecektir. Ahşap malzemenin mekanik anlamda birleşimindeki bu yeni metod, ileri teknoloji sayesinde birçok mühendislik uygulamalarında kullanılabilir
Sürtünme Kaynak Yöntemi Uygulamalarında Ahşap Esaslı Malzemelerinin Kullanımının İncelenmesi
1059B191800412
Keywords: Composite and Hybrid Materials; Kompozit ve Hibrit Malzemeler